2000
DOI: 10.1161/01.cir.102.14.1703
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Microscopic Localization of Constitutive and Heat Shock–Induced Proteins HSP70 and HSP27 in the Rat Heart

Abstract: Background-Heat-shock treatment of rats elevates expression of heat-shock proteins, which play a role in improving the contractile recovery and reducing infarct size in hearts after ischemic injury. However, the location of these proteins in the heart is unknown. Methods and Results-Anesthetized rats were heat-shocked by elevation of body temperature to 42°C to 42.5°C for 15 minutes, followed by 24 hours of recovery. Control and heat-shocked hearts were extirpated and perfused briefly with saline followed by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 44 publications
4
36
0
2
Order By: Relevance
“…At 24 h after heat shock treatment, the Hsp27 distribution and abundance are minimally changed (40). In the current study, the abundance of Hsp27 is not significantly changed in the heart after insulin, heat shock, or heat shock and insulin treatments (Fig.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…At 24 h after heat shock treatment, the Hsp27 distribution and abundance are minimally changed (40). In the current study, the abundance of Hsp27 is not significantly changed in the heart after insulin, heat shock, or heat shock and insulin treatments (Fig.…”
Section: Discussionmentioning
confidence: 40%
“…In contrast, at 1 h after heat shock, Hsp70 was detectable in cardiac tissue and appeared to be localized mostly in small capillaries and in perivascular cells between the cardiomyocytes (Fig. 3), and this localization is not different at 6 or 24 h after heat shock (40,42,43). At 1 h after induction, it is unlikely that sufficient mature Hsp70 has accumulated in the cells to provide protection from ischemiareperfusion injury.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Alternatively, a recent study with confocal microscopy demonstrated that heat shock-induced stress-protein expression in rat heart increases HSP70 expression in microvascular blood vessels and not in cardiomyocytes (18). This study suggests that the cross tolerance to I/R injury after heat shock, mediated by HSP70 expression in the myocardium, may involve alterations in microvascular blood flow during ischemia or following restoration of flow to ischemic areas during reperfusion.…”
Section: Discussionmentioning
confidence: 86%